2009
DOI: 10.1002/jrs.2175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical Raman and surface‐enhanced Raman scattering study of cysteine

Abstract: Raman spectra in solid and 1 M solution of L-cysteine and surface-enhanced Raman scattering (SERS) spectra of this molecule in the zwitterionic form, by using colloidal silver nanoparticles, have been recorded. Density functional theory with the B3LYP functional was used for the optimizations of the ground state geometries and simulation of the vibrational spectrum of this amino acid. The SERS spectrum with a large silver cluster as a model metallic surface was simulated for the first time. Taking into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
96
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 48 publications
(48 reference statements)
15
96
1
Order By: Relevance
“…Fleming et al have studied SERS of cysteine from both experimental and theoretical perspectives. [27] The authors confirm the presence of gauche (PH) and trans (PN) rotamers in the solid state, the formation of a S-S bond in the solution state, the dissociation of the peptide bond and mixing of rotamers because of the SERS effect, and the relative importance of the interaction of sulfhydryl, NH 3 + , and carboxylate groups with the metallic surface. The adsorption of tri-methyl phosphine (TMP) on colloidal silver was investigated by means of SERS by Hu et al [28] On the basis of surface selection rules, it was deduced from the SERS that TMP adsorbs on silver surface via its P atom.…”
Section: Theoretical Aspects Of Sersmentioning
confidence: 64%
“…Fleming et al have studied SERS of cysteine from both experimental and theoretical perspectives. [27] The authors confirm the presence of gauche (PH) and trans (PN) rotamers in the solid state, the formation of a S-S bond in the solution state, the dissociation of the peptide bond and mixing of rotamers because of the SERS effect, and the relative importance of the interaction of sulfhydryl, NH 3 + , and carboxylate groups with the metallic surface. The adsorption of tri-methyl phosphine (TMP) on colloidal silver was investigated by means of SERS by Hu et al [28] On the basis of surface selection rules, it was deduced from the SERS that TMP adsorbs on silver surface via its P atom.…”
Section: Theoretical Aspects Of Sersmentioning
confidence: 64%
“…6. The observed frequencies are tabulated in Table 3 along with their assignment based on the literature and DFT calculations [7][8][9][46][47][48][49]. The most prominent bands in the FT-Raman spectrum of L-Cys is in the region of 2550-3000 cm À 1 and in the region of 500-1700 cm À 1 .…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…In the metal surfaces, 7-AI and L-Cys binds that leads to induce the surface dipoles, causing a change in the work function of the metal [3]. Recently, 7-AI and L-Cys molecules have been deposited on the surface of different metallic nanoparticles [4][5][6][7][8][9][10][11][12][13]. This interaction can be analyzed by means of vibrational spectroscopy because it provides more specific information of the adsorbate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been recently recognized that in contrast to the large plasmon active supportive nanoparticles used in SERS, small Ag n (n ¼ 1-6) clusters are equally suitable probes for biomolecular sensing [12][13][14][15]. It has been found that silver clusters with only few atoms give rise to scaffold specific single molecule Raman signals [6,16,17] because of their specific interactions with biomolecules and therefore can be used as ideal probes for the biomolecular environment. Several studies were devoted to the positively charged silver-analine hybrid complex [11,14,16,[18][19][20][21][22][23].…”
mentioning
confidence: 97%